1986
DOI: 10.1088/0029-5515/26/4/001
|View full text |Cite
|
Sign up to set email alerts
|

Rotation scalings and momentum confinement in neutral-beam-injected ISX-B plasmas

Abstract: Scalings of the central rotation in non-gettered, co-injected ISX-B discharges have been measured as a function of beam power, electron density and plasma current. Extensive studies are made possible by exploiting charge-exchange excitation (CXE) of 0 VIII lines to measure Doppler shifts. The rotation velocity, vϕ(0), tends to saturate at (1.0 − 1.2) × l07 cm·s−1 when Pb≅0.5 MW, showing little further increase up to the maximum input of 2 MW; vϕ(0) is independent of ne and Ip. Momentum confinement times in qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…(33) predicts that T decay > TJ. Decay constants are substantially larger than momentum confinement times in experiments where both are measured [3,6], which is qualitatively consistent with Eq. 33and a rapidly decreasing density.…”
Section: Velocity Decay Measurementssupporting
confidence: 78%
See 2 more Smart Citations
“…(33) predicts that T decay > TJ. Decay constants are substantially larger than momentum confinement times in experiments where both are measured [3,6], which is qualitatively consistent with Eq. 33and a rapidly decreasing density.…”
Section: Velocity Decay Measurementssupporting
confidence: 78%
“…An extensive set of central rotation velocity measurements, including a number of parameter dependences, was made on ISX-B [3]. The analysis, based on gyroviscous theory for the transfer of input torque, was able to explain these data [12].…”
Section: Isx-b Experiments and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis had shown a relationship between energy and momentum confinement [3,4,5,6,7]. It is often reported that these quantities have comparable magnitudes and have similar dependencies with individual plasma parameters.…”
Section: Introductionmentioning
confidence: 97%
“…Typical values of the rotation velocity with neutral beam input are in the range of a few x 10' cm/s. Some toroidal rotation during purely ohmic plasmas has been observed [1,5,7,14], and there have been some ancillary measurements of toroidal rotation during the ohmic phase of neutral beam plasmas [2,3,4,6,10]. The ohmic results are summarized in Table I.…”
mentioning
confidence: 99%